A Novel Synthesis Pathway for Silver Nanoparticles Using Anthurium Bipinnatifidum - Ratri, Monica Cahyaning; Ipung, Kadek Erland Puba; Darmawan, Bobby Aditya (Department of Chemistry Faculty of Science and Technology Walisongo, 2024)
The field of nanomaterial synthesis has grown substantially in recent years. However, many existing synthesis methods have significant drawbacks, such as the use of organic solvents that are harmful to the environment and the high cost of inorganic reducing agents. To address these issues, we developed a simple and cost-effective method for synthesizing silver nanoparticles (AgNPs) using Anthurium bipinnatifidum extract as a reducing agent and water as a green solvent. This green chemistry approach offers a quick and straightforward synthesis process, with the optimum incubation time and volume were 1 hour and 0.5 mL, respectively. The results of this new method show promising characteristics, as demonstrated by SEM, UV-Vis spectrophotometry, and FTIR analyses. Additionally, the surface plasmon resonance (SPR) of the synthesized AgNPs was observed at 431 nm, which aligns with the typical SPR for AgNPs. The particles formed were spherical, with sizes ranging from approximately 40 to 80 nm. This research establishes an efficient new procedure for AgNPs synthesis with excellent outcomes.